Mushroom flavour - Moliszewska, Ewa (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
Mushrooms and fungi not only present a fascinating world of shapes, both macro- and microscopic, but they are also an interesting source of flavours, fragrances and odours, e.g. garlic, coconut, flour-like, cucumber or fruit-like, as well as the most characteristic for this kingdom of living organisms mushroom-like flavour and aroma. Fungi can possess many different and interesting flavours and fragrances – starting from nice anise-like, fruit-like, cucumber, garlic, to cheese-garlic, and ending with potato or flour-like smells. Some mushrooms emit carbide or distinctly faecal-like odour. The taste of mushrooms is frequently correlated with their aroma. What components does the core of a mushroom flavour consist of? Chemical analysis of specimens reveals compounds responsible for characteristic flavour and odour. It was found that the most characteristic flavour compound is defined mainly by C8 volatiles. Between all C8 compounds the most important for mushroom flavour are oct-1-en-3-ol, octan-3-ol, octan-3-on and oct-1-en-3-on. Fungi and mushrooms can enable biotechnological production of some flavour components, for instance the Nidula niveotomentosa produces a characteristic raspberries compound – raspberry ketone in submerged cultures; the biotechnological production can also provide rare and tasty forest mushroom biomass e.g. edible boletus.